The Workshop on Cattle Breeding and Fattening in an Effort to Increase the Human Development Index in Sijunjung Regency - Putri, Santi Diana; Meidita, Fadilla -; Alatas, Andi; Yulkifli, Yulkifli; Fevria, Resti; Dona, Afrini; Elisia, Rini (Fakultas MIPA Universitas Negeri Padang, 2024)
The Human Development Index (HDI) is an important indicator to measure a country's progress in improving the welfare of its people. Compared to other Southeast Asian countries, Indonesia's HDI is still low. To improve Indonesia's HDI, the livestock sector, especially cattle breeding and fattening, can contribute significantly. ICMI (Indonesian Muslim Scholars Association) in collaboration with the Department of Agroindustry developed a high-quality and sustainable cattle breeding and fattening program. The goal of this collaboration is to improve cattle breeding and raising skills and support sustainable agricultural development. The solution of this collaboration is the improvement of participants' knowledge and skills on better livestock technology so as to increase the productivity and quality of beef cattle especially in Sijunjung Regency.